There's money to be made in agriculture_Chief Audu Ogbe_HMA - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Agriculture has a future and those who want to embrace the sector should know there is money to make in agriculture. #IITA50 has developed many technologies, for example, Nigeria can quadruple yam production with some of these technologies », Chief Audu Ogbey, Nigeria Minister for Agriculture and rural development appreciates #IITA50 Agricultural transformation in Nigeria and Africa in general.